Konsep dan Implementasi Produksi Halal pada UMKM: Tinjauan Pustaka Ekonomi Syariah - Hali Hali; Muhammad Aditya Saputra; Ganis Khairulysa Prasetiyo; Lina Marlina (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study explores the concept and practical implementation of halal production in Micro, Small, and Medium Enterprises (MSMEs) through the lens of Islamic economics. Employing a qualitative literature review approach, it synthesizes findings from previous studies on Islamic production theory, halal assurance systems, and the economic role of MSMEs in Indonesia. The analysis reveals that halal production encompasses not only compliance with Islamic jurisprudence but also ethical, environmental, and social dimensions, emphasizing justice, transparency, and sustainability in business operations. For MSMEs, adopting halal production practices can strengthen consumer confidence, improve competitiveness in both domestic and global markets, and contribute to national economic resilience. Nonetheless, challenges persist, including a limited understanding of halal standards among entrepreneurs, high certification costs, and inadequate access to institutional and governmental support. Addressing these issues requires an integrated strategy involving collaboration among policymakers, halal certification authorities, and MSME actors. This study concludes that empowering MSMEs through education, digital innovation, and regulatory reinforcement is vital to achieving a sustainable and inclusive halal economy aligned with the principles of Islamic ethics.